Corporate Communication and Organizational Performance: A Study in Commercial Banks in Kenya - Kitemu, Paul Muteti; Sang, Anne; Wachira, Anita (Journal Integration of Management Studies, 2024)
The research delves into the influence of corporate communication on the organizational performance of commercial banks in Kenya, prompted by the sector's persistent decline despite its substantial number of licensed institutions, with only a handful dominating the market. The predominant focus on financial metrics has overshadowed the concerns of vital stakeholders such as employees, customers, communities, and regulators. Using a descriptive cross-sectional approach, data were gathered from 394 respondents across 39 banks via a questionnaire, which was then analyzed using SPSS. The findings reveal a significant correlation between corporate communication and banks' performance, suggesting that ineffective communication during corporate changes significantly contributes to performance decline. The study proposes the integration of corporate communication into corporate change strategies, a priority set by senior management, to drive comprehensive organizational performance and address stakeholders' needs, thereby fostering sustainable growth and expansion opportunities for banks.